Sharing Hanukkah - McDonnell, Janet, 1962-; Magnuson, Diana (Chicago : Childrens Press, 1993)
Visiting his Jewish friend David, Michael hears the story of Hanukkah, tastes latkes, watches the lighting of the menorah, and plays a few games of dreidel.
2.6
K-3
Keywords: Hanukkah -- Fiction; Jews -- Fiction; Hanukkah -- Fiction; Jews -- Fiction